2021
DOI: 10.1111/hsc.13694
|View full text |Cite
|
Sign up to set email alerts
|

Voicing the perspectives of stroke survivors with aphasia: A rapid evidence review of post‐stroke mental health, screening practices and lived experiences

Abstract: A rapid evidence review (RER) of empirical literature was conducted to explore aphasic stroke survivors' mental health outcomes and lived experiences, as well as the screening instruments for this cohort. The RER was informed by a critical disability theory approach and synthesised qualitative and quantitative evidence within and across 29 studies, published between 2000 and 2021, from a systematic search of three databases. Understanding the relationship between post-stroke aphasia and mental health outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
(259 reference statements)
0
5
0
Order By: Relevance
“…It should not be accepted as normal that people with stroke navigate the reconstruction of self and life on their own, with little support, 67 feeling isolated and abandoned by stroke services 68 . We contend that it should not be seen as inevitable that people have significant reductions in friendships, 11 and quality of life, 69 or that 20% of people experience anxiety after stroke 70 and 30% experience depression 71 —rates doubled if someone has aphasia 72 . This raises pressing questions about the overarching objectives and priorities of current stroke service approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should not be accepted as normal that people with stroke navigate the reconstruction of self and life on their own, with little support, 67 feeling isolated and abandoned by stroke services 68 . We contend that it should not be seen as inevitable that people have significant reductions in friendships, 11 and quality of life, 69 or that 20% of people experience anxiety after stroke 70 and 30% experience depression 71 —rates doubled if someone has aphasia 72 . This raises pressing questions about the overarching objectives and priorities of current stroke service approaches.…”
Section: Discussionmentioning
confidence: 99%
“… 68 We contend that it should not be seen as inevitable that people have significant reductions in friendships, 11 and quality of life, 69 or that 20% of people experience anxiety after stroke 70 and 30% experience depression 71 —rates doubled if someone has aphasia. 72 This raises pressing questions about the overarching objectives and priorities of current stroke service approaches. We ask whose needs are being served by current approaches to stroke service delivery and whose needs are not being met?…”
Section: Discussionmentioning
confidence: 99%
“…There is, however, an evidence-practice gap in the consistent and sustained provision of low-intensity psychological care after stroke and aphasia. Further research into how to address this gap is a priority (Kristo and Mowll 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent research argues that the consequential negative social participation impact arising from aphasia, such as social exclusion, isolation, and depression, have equally profound ramifications as aphasia itself (Moss et al, 2021). Compared to people without post-stroke aphasia, people with aphasia (PwA) are at higher risk of detrimental psychosocial outcomes such as poor self-perception, social isolation, and loneliness (Kristo & Mowl, 2022). Baker et al (2019) report that post-stroke PwA self-reported negative mood changes and trauma related to their communication impairment, regardless of a formal diagnosis of depression.…”
Section: Introductionmentioning
confidence: 99%